Bivalve sentinels sound the alarm: Rare earth elements patterns along the Mediterranean coast - Silvia Secco; Giulia Cesarini; Leonardo Marcello; Giovanni Libralato; Antonella Giarra; Alessandra Marano; Marco Trifuoggi; Massimiliano Scalici (Environmental Pollution, 2026)

Plastic pollution in aquatic ecosystems: publication trends and overview of the special issue - Giulia Cesarini; Massimiliano Scalici; Timothy Hoellein; Paula Sobral; Verónica Ferreira (Hydrobiologia, 2026)

Development of a machine learning tool for the enhancement of carbon footprint prediction for cattle milk production - Lorena Foschi; Diego Pennino; Giulia Gislon; Giampiero Grossi; Alberto Mantino; Marco Barbanera; Marco Marconi; Francesco Cesarini; Chiara Rossi; Andrea Vitali; Anna Sandrucci; Maddalena Zucali; et al. (The International Journal of Life Cycle Assessment, 2025)
Purpose The combination of machine learning (ML) and life cycle-based methodologies is a promising strategy to overcome some of the most relevant issues regarding carbon footprint (CF) calculation/prediction. This research presents an approach and a software tool to apply ML techniques with the aim of solving issues related to data availability in the life cycle inventory (LCI) and improving the accuracy of carbon footprint predictions. The final purpose is to streamline the CF calculation process in the dairy cattle farming sector. Methods The methodology used in this study consists of three steps: dataset creation, data optimization, and enhanced prediction. Initially, a dataset was compiled from primary sources and literature on LCA studies related to dairy cattle farming. This dataset contained missing data that could affect prediction accuracy. ML techniques were then applied to improve the quality of the data. A ML tool implementing 11 different regression algorithms was developed. This user-friendly tool, easily accessible also to non-ML experts, automatically optimizes data quality by determining the most appropriate algorithm for predicting missing values on a case-by-case basis. In the final step, the same tool was used on the optimized dataset to identify and use the best model for accurate CO 2 -eq emissions prediction. Results and discussion An initial assessment was conducted to evaluate the accuracy of a ML model. The results of the test demonstrated that the Gaussian kernel regression model exhibited the highest performance among the available models, with a root mean square error (RMSE) of 18.87%. This value will be used as a threshold for the assessment of the efficacy of the described approach. The tool was then employed to optimize the dataset by predicting missing values. Lastly, the tool was utilized to predict CO 2 -eq emissions once more, but this time using the optimized dataset for training. As with the previous test, the Gaussian model exhibited the highest performance, but this time with a RMSE of 14.65%. The RMSE was 4% lower, thereby reflecting an increased accuracy in the prediction. Conclusions The results demonstrate that the presented ML-based approach and tool are effective in predicting lacking inventory data, as well as in improving the accuracy and reliability of CO 2 -eq emissions prediction in life cycle-based studies. The developed tool makes ML more accessible to non-expert users and facilitates usability. This integration of ML and life cycle-based methodologies shows promising avenues for more accurate and efficient environmental impact assessments in agriculture.

Beyond the flow: ecological insights from diatom communities of a Mediterranean intermittent river - Davide Taurozzi; Giulia Cesarini; Carmela Di Santo; Massimiliano Scalici (Environmental Research, 2025)

Multi-matrix approach to microplastic pollution in the bivalve Donax trunculus, sediment and water along the Mediterranean coasts - Silvia Secco; Giulia Cesarini; Luca Gallitelli; Giuseppe Suaria; Andrea Paluselli; Michael Di Gioacchino; Armida Sodo; Massimiliano Scalici (Environmental Pollution, 2025)

First Assessment of Freshwater Monitoring Under the Eu National Emission Ceilings Directive: Emerging Issues and Way Forward - Giulia Cesarini; Riccardo Fornaroli; Angela Boggero; Simona Musazzi; Silvia Zaupa; Elzbieta Dumnicka; Aldo Marchetto; Michela Rogora (Water, Air, & Soil Pollution, 2025)
Air pollution has significantly increased during the Anthropocene, adversely affecting ecosystems and human health. The National Emission Ceilings Directive (NECD, 2016/2284/EU) set targets for reducing emissions and required Member States to establish a national monitoring network to assess ecosystem changes due to air pollution. For freshwaters, the NECD monitoring focused on assessing effects of sulphur and nitrogen deposition and acidification status using chemical parameters and sensitive biological indicators. This paper evaluates the present NECD monitoring scheme and its applicability in Italy, from site selection to initial data collection. High mountain lakes were selected as study sites, because they are free from direct human impacts and sensitive to air pollutant deposition. A two-year survey of chemical and biological components (diatoms and macroinvertebrates) was conducted in eight lakes with the aim to (1) assess the suitability of chemical parameters and biological indices for evaluating air pollutant impacts on sensitive water bodies in Italy, focusing on acidification and nitrogen enrichment, and (2) discuss the current approach's achievements and limitations. Results highlighted the need to develop specific indices for detecting atmospheric pollution impacts on freshwater ecosystems. Beside acidification, other drivers, including nutrients, proved to be important in shaping mountain lakes biological assemblages and affecting their response to pollutant deposition. Our study contributed to a critical assessment of the present freshwater monitoring under the NECD from the Italian perspective, providing indications on future improvement and development of the monitoring scheme itself.

Macroplastic colonization by macroinvertebrates in a Mediterranean wetland: A biodiversity enrichment opportunity - Davide Taurozzi; Giulia Cesarini; Massimiliano Scalici (Anthropocene, 2025)

Computing riverine inputs of macrolitter into the Central Tyrrhenian Sea (Western Mediterranean Sea) from the Tiber River during the 1st post-pandemic year - Giulia Cesarini; Antonella Arcangeli; Massimiliano Scalici; Roberto Crosti (Science of The Total Environment, 2025)

Interconnected impacts of water resource management and climate change on microplastic pollution and riverine biocoenosis: A review by freshwater ecologists - Silvia Quadroni; Giulia Cesarini; Vanessa De Santis; Silvia Galafassi (Journal of Environmental Management, 2024)

Riparian vegetation entraps macroplastics along the entire river course: Implications for eco-safety activities and mitigation strategies - Luca Gallitelli; Maurizio Cutini; Giulia Cesarini; Massimiliano Scalici (Environmental Research, 2024)

Testing effectiveness in nature reserve management using GIS-based tools: a 25 years monitoring of land use change in a Mediterranean coastal wetland - Flavio Marzialetti; Giulia Cesarini; Alicia T. R. Acosta; Corrado Battisti (Wetlands Ecology and Management, 2024)
Land-cover change dynamics were investigated in a Mediterranean coastal wetland to evaluate the long-term effectiveness of nature reserve management. A multitemporal analysis of land cover maps was conducted, utilizing visual interpretation of aerial orthophotos from the summer seasons of 1996, 2008, 2015, and 2021. Landscape changes were evaluated by transition matrices and chord diagrams. Maps were classified in accordance with CORINE land cover types at a fourth level of detail. The multitemporal analyses provided a comprehensive overview of landscape changes within the reserve over the past 25 years. The most notable changes were the increase of wetland areas and the reduction of agricultural and artificial areas. Moreover, seminatural vegetation constantly extended over time. These changes reflected the continuous management activities within the nature reserve, encompassing agreements for water supply, restoration projects, and measures to counteract illegality. These operational actions induced fine-grained ecological changes (outcomes at ecosystem level). This study highlighted the importance of remote sensing and landscape analysis, matched with fine-grained management data, as tool for long-term monitoring. Such an approach provides valuable support in evaluating the effectiveness of strategies promoted in nature reserves hosting wet coastal ecosystems of high conservation concern.

Anthropogenic litter in a Mediterranean coastal wetland: A heterogeneous spatial pattern of historical deposition - Corrado Battisti; Giulia Cesarini; Luca Gallitelli; Filippo Moretti; Massimiliano Scalici (Marine Pollution Bulletin, 2024)

Diatom and macroinvertebrate communities dynamic: A co-occurrence pattern analysis on plastic substrates - Davide Taurozzi; Giulia Cesarini; Massimiliano Scalici (Science of The Total Environment, 2024)

Teratogenic effects of environmental concentration of plastic particles on freshwater organisms - Giulia Cesarini; Silvia Secco; Davide Taurozzi; Iole Venditti; Chiara Battocchio; Stefania Marcheggiani; Laura Mancini; Ilaria Fratoddi; Massimiliano Scalici; Camilla Puccinelli (Science of The Total Environment, 2023)

Nanoplastic exposure inhibits feeding and delays regeneration in a freshwater planarian - Giulia Cesarini; Francesca Coppola; Diana Campos; Iole Venditti; Chiara Battocchio; Andrea Di Giulio; Maurizio Muzzi; João L.T. Pestana; Massimiliano Scalici (Environmental Pollution, 2023)

New ecological frontiers in the plastisphere: Diatoms and macroinvertebrates turnover assessment by a traits-based approach - Davide Taurozzi; Giulia Cesarini; Massimiliano Scalici (Science of The Total Environment, 2023)

Hydromorphological discontinuities deeply modify the benthic multi-species assemblage diversity in a Mediterranean running river - Giulia Cesarini; Luca Gallitelli; Lorenzo Traversetti; Tiziana Bandini; Massimiliano Scalici (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

From city to sea: Spatiotemporal dynamics of floating macrolitter in the Tiber River - Giulia Cesarini; Roberto Crosti; Silvia Secco; Luca Gallitelli; Massimiliano Scalici (Science of The Total Environment, 2023)

Epiplastic microhabitats for epibenthic organisms: a new inland water frontier for diatoms - Davide Taurozzi; Giulia Cesarini; Massimiliano Scalici (Environmental Science and Pollution Research, 2022)
Plastic pollution is widespread in each type of ecosystems. However, the colonization events of microorganisms on plastics seem to be neglected in inland waters. Therefore, in this study we analyze the possible colonization on the surface (hereafter epiplastic microhabitats) of two typology of plastic supports by diatom community. Specifically, we located 20 supports in expanded polystyrene and 20 in polyethylene terephthalate both floating and dipped (~ 1 m) in a central Italian shallow water pond, in order to evaluate the diachronic colonization of diatoms from November 2019 to August 2020. Our result showed the tendency in colonizing both epiplastic microhabitats without significant differences in number of species; additionally, depth does not appear to affect the number of species. As regard the temporal colonization, the number of species tends to increase over time from autumn-winter to spring-summer in both types of epiplastic microhabitats and depth. Instead, increase in dominance of some species over time has been demonstrated: only a few species keep a high number of individuals compared to the others; therefore, the number of individuals within the species is not uniformly distributed. These results suggest the tendency of diatom community to colonize plastic supports in lentic waters, and this evidence can be very important because artificial supports can increase the surface available for the settlement of the algae community with an increase of productivity and the colonization of new communities of different taxa. Further studies are mandatory to investigate the possible effects on the epiplastic community and the ecological implications in freshwater environments.